Big Nate : remain calm! - Peirce, Lincoln (Peirce, Lincoln. Big Nate, 2024)
"Middle school can be a hot mess--especially for sixth-grader Nate Wright. Whether he's bluffing his way through an oral report about...umm...some random war, peer-reviewing a classmate's story about cats, or writing a book report on a literary gem called The Cheerleader Chronicles, Nate's usually up to his eyeballs in stress. But our hero always finds ways to cope. Like bringing Spitsy to school as an emotional support dog. Or creating a graphic novel to (sort of) complete his math homework. Nate even authors a no-nonsense advice column with a title that says it all: Ask The Genius. So take a tip from P.S. 38's resident renaissance man: When problems start piling up, do what Nate does: REMAIN CALM!"--